Faculty Engagement and Performance Improvement in Engineering Students - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2025)
The concept of faculty engagement has become prominent in engineering education. The faculty members have to act as architects of effective engineering programs to implement efficient student engagement. Fifteen issues have been selected in the student engagement process based on prominent research works. 31 senior faculty members have been selected for this research work and questionnaires have been distributed to them to give feedback on the current status of faculty engagement. Based on their feedback a draft model of faculty engagement has been developed. There is a need for further field-specific validation by a large number of engineering faculty members. This is a current limitation of the model. There are many preconditions like strategic planning, availability of needed resources, and need-based faculty development for the implementation of the model.